Responses of testate amoebae assemblages (Amoebozoa: Arcellinida) to recent volcanic eruptions, inferred from the sediment record in Laguna Verde, southern Patagonia, Argentina - Charqueño Celis, Norma Fernanda (2021)
There is little knowledge about testate amoebae in lakes and their responses to volcanic eruptions. To address this knowledge gap, we studied the paleoecology of these protists in a sediment record from Laguna Verde, a lake located east of the southern Patagonian Ice Field, in Santa Cruz Province, Argentina. The lake is under the influence of volcanic eruptions from Lautaro Volcano, Chile, ~ 42 km WNW of Laguna Verde. We evaluated the response of 11 testate amoeba morphospecies in the lake to the last four Lautaro eruptions, using a 61-cm sediment core. Calcium (Ca), a major element of volcanic ash, was the most important variable explaining testate amoeba variability in the three zones determined by detretended correspondence analysis. We identified four declines in testate amoeba abundance and diversity associated with tephra deposition. Poisson regression analysis revealed that Difflugia immanata, D. bidens, and D. glans strain “glans” decrease after deposition of tephra layers. In contrast, Centropyxis constricta strain “constricta,” C. aculeata strain “aculeata” and Zivkovicia compressa respond positively to ash deposition. Our findings suggest a high resilience of testate amoebae to stochastic events such as volcanism because the same assemblage (D. immanata, D. bidens, and D. glans strain “glans”) inhabited the lake before and after the ashfalls. Nevertheless, several volcanic eruptions during the last ~ 300 years may have weakened this resilience and had a long-term effect on community diversity. Multivariate analysis showed that potassium (K) plays a significant role in shaping assemblage composition. Because of the low K content of the Lautaro tephra, we infer that higher potassium concentrations in sediments are not related with volcanic events, but rather, are associated with terrestrial input. Future studies, however, will be needed to identify the source of K in the sediment record and its relationship with testate amoebae assemblages. Our study demonstrates the potential for using lacustrine testate amoebae as environmental proxies, and illustrates the direct effects of volcanic ash deposition on their assemblage composition, diversity and distribution in southern Patagonia.